Management accounting and human behaviour / Aris Kefli Mohamad Yusof - Mohamad Yusof, Aris Kefli (1992)
Management accounting is an information system which should help managers to plan and control the resources of their business organization, so as to achieve the objective of the organisation. However, information is valuable only if it is interpreted correctly and used purposefully by managers and employees; in other words, it is necessary to ensure that management accounting system stimulate efficient management decision making there ara different accounting techniques and system for providing relevant planning and control information. We must now give some thought must be given to the problem of ensuring that the manager's decision is influenced properly by the information they receive. The correct use of information depends not only on the content of the information itself, but also on the behavior of its recipient